Ground Water Conditions Around The Trunk Of Pollution Palangki Gold Mining District In District IV Nagari Sijunjung - Putri, Reza; Juita, Erna; Farida, Farida (STKIP PGRI Sumbar, 2013)
Â This study aims to obtain data on the physical condition of the soil water (temperature , color , odor , taste and turbidity ) and chemical conditions ( lead ( Pb ) , Mercury water ( Hg ) , chromium ( Cr ) , copper ( Cu ) , and acidity ( pH ) . Water the soil around the stem Palangki mining pollution in the District IV District Nagari Sijunjung with 4 sample points are Kenagarian Palangki , Muaro Bodi , New Koto and Mundam Sakti. determined to be based interval in sampling the river.Methods are applied that analysis descriptive whit the aim of making a systematic overview vaktual and accurate information on the factors and relationship properties to be studid.Based on observations and laboratory tests that the quality of groundwater in the District IV Nagari : 1 ) physical conditions , parameters of the water temperature at the sample point that meets most standard color , odor , taste and turbidity at all sample points have met the standards PERMENKES NO.907/MENKES / SK/VII/2002 . 2 ) the condition of chemical parameters of lead, mercury , chromium and copper have met the Minister of Health standards , while the acidity of the water only partially meets the standards PERMENKES NO.907/MENKES/SK/VII/2002 . Based on the results of this study groundwater conditions around the stem Palangki physical and chemical standards are in Permenkes 2002, but to reduce the acidity pH needs to be done in some places the ground water treatment before it is used by the public .Â